Cytological analysis of Kepok Abu Polyploid's Banana Plantlets (Musa paradisiaca L.) Due to Colchicine's Application in Tissue Culture Media - istiqomah, Istiqomah; Wahyuningsih, Sri; Ernawiati, Eti; Agustrina, Rochmah (Biosfer: Jurnal Tadris Biologi, 2021)
This research aimed to determine the mitotic abnormalities, changes in the number of chromosomes, mitotic index, and the number and length of kepok abu banana plantlet roots due to administration of 0.1% colchicine in tissue culture media. This research was performed at the Botanical Laboratory of the Biology Department, Faculty of Mathematics and Natural Sciences, UNILA. This research compared the cytology by employing the Squash method between root tip cells of kepok abu banana plantlets after administering 0.1% colchicine and the control group. The researchers analyzed the data descriptively and presented them in tables and bar charts. The results showed that the administration of 0.1% colchicine resulted in mitotic abnormalities. It also increased the number of chromosomes in the controls 2n=3x and 2n=3x+4. The mitotic index decreased, and the average number of roots was lower. However, the size was longer compared to the control group.